Pengaruh Rekrutmen, Seleksi, dan Pengembangan Sumber Daya Manusia Terhadap Kinerja Karyawan pada PT Tangan Kita Berkarya - Andre Yanto; Rifki Suwaji (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
Effective human resource management is a key factor in improving employee performance and maintaining company competitiveness, especially amidst the demands of increasingly dynamic work environments. Problems frequently faced by companies relate to inaccurate recruitment processes, suboptimal selection processes, and unsustainable human resource development, resulting in low employee performance. Based on these conditions, this study aims to analyze the influence of recruitment, selection, and human resource development on employee performance at PT Tangan Kita Berkarya. This study uses a quantitative approach with a survey method through the distribution of questionnaires to employees. The collected data were analyzed using multiple linear regression with the help of SPSS, after first undergoing validity, reliability, and classical assumption tests. The results show that recruitment and selection each have a positive and significant effect on employee performance. Human resource development also has a positive and significant effect and is the variable with the strongest contribution to performance improvement. Simultaneously, these three variables have a significant effect on employee performance. These findings indicate that improving employee performance requires integrated human resource management, from the recruitment process to continuous employee development.